DIVERSITY OF SOIL BORN ESTARCH HYDROLYZING FUNGI OF LIVESTOCK FARMS - S. Sana; A. A. Anjum; M. Nawaz; 1Mansur-ud-Din Ahmad; M. Rabbani (Journal of Animal and Plant Sciences, 2017)
Soil of livestock farms is rich with mycoflora having diverse biological activities. Fungi isolated from soil (n=145) of livestock farms (n=29) at Lahore district were characterized into pathogenic, toxigenic and phaeoid starch hydrolyzers. Pure fungal isolates (1101) recovered from soil cultured on starch agar and only 112 (10.17%) were positive to starch hydrolysis. Out of 112 starch hydrolyzing fungi, 32 (28.57%) were declared pathogenic. Non-pathogenic starch hydrolyzing fungi further screened for mycotoxin production potential and 27.5 percent were found toxigenic. Starch hydrolyzing non-toxigenic fungi (n=58) were morphologically identified as Aspergillus, Penicillium, Fusarium, Zygomycete, Actinomycete and Phaeoid.  Highest number of industrially important fungi was of Aspergillus (27.58%). Aspergillus isolates (n=16) identified at specie level were A. niger (03), A. flavus (07), A. versicolor (01), A. terrus (04) and A. nidulans (01). These isolates were declared as safe and could be used for mass production of amylases to meet commercial demands.
Keywords: Livestock farms; fungi; starch hydrolysis; non-toxigenic and Aspergillus species